New Insights into the Pathogenesis of Preeclampsia – The Role of Nrf2 Activators and their Potential Therapeutic Impact - Kweider, N.; Wruck, C. J.; Rath, W. (Geburtshilfe und Frauenheilkunde, 2013)
Preeclampsia (PE), characterized by proteinuric hypertension and occurring in 2–3 % of all pregnancies, is one of the leading causes of maternal, fetal and neonatal morbidity and mortality. The etiology of PE still remains unclear and current treatments for this devastating disorder are still limited to symptomatic therapies. Placental oxidative stress may be a key intermediate step in the pathogenesis of PE; it has been related to excessive secretion of multiple antiangiogenic factors, mainly soluble fms-like tyrosine kinase-1 (sFlt-1) and soluble endoglin (sEng). The nuclear factor-erythroid 2-like 2 (Nrf2) pathway is one of the most important systems that enhance cellular protection against oxidative stress. Nrf2 serves as a master transcriptional regulator of the basal and inducible expression of a multitude of genes encoding detoxification enzymes and antioxidative proteins. Evidence for a link between Nrf2 and restoring the balance between pro- and antiangiogenic factors mainly through its downstream target protein heme oxygenase-1 (HO-1) has lately been discussed. HO-1 metabolizes heme to biliverdin, iron and carbon monoxide (CO). CO enhances vascular endothelial growth factor (VEGF) synthesis in vascular smooth muscle and promotes its relaxation and hence vasodilatation. In addition, HO-1 has been shown in vitro to inhibit the production of sFlt-1. A recent animal study demonstrated that the induction of HO-1 in a mouse model of PE attenuates the induced hypertension in pregnant mice. This provides compelling evidence for the protective role of Nrf2/HO-1 in pregnancy and identifies this pathway as a target to treat women with PE. We summarize the recent findings on the involvement of Nrf2 in the pathogenesis of PE, and provide an overview of the possible beneficial effects of Nrf2 inducers in PE.
Keywords: preeclampsia; Nrf2; heme oxygenase-1